CURRENT TRENDS IN FORMATION OF URINARY SYSTEM DISEASES IN SCHOOL AGE CHILDREN AND FEATURES OF THEIR COURSE - Tajieva Zebo Bahodirovna (Galaxy International Interdisciplinary Research Journal, 2022)
In the complex treatment of acute and chronic kidney diseases in children, diet therapy plays an important role. High requirements are imposed on therapeutic nutrition, since the kidney is the main organ for the excretion of metabolic products that come with food and are formed as a result of the breakdown of body tissues, as well as the organ responsible for maintaining the constancy of the internal environment. Under certain conditions, it becomes necessary to correct in the diet of nutrients such as animal protein, gluten, oxalates, urates, phosphates, the metabolic products of which are excreted through the kidneys and affect not only the pathogenetic mechanisms of the development of the disease, but also participate in the formation of non-immune processes of progression disease to the stage of renal failure.